Pengaruh Terapi Rendam Kaki Air Hangat terhadap Penurunan Tekanan Darah dan Penurunan Tingkat Depresi dengan Hipertensi di Panti Sosial Lanjut Usia Harapan Kita Palembang Tahun 2022 - Nurhidayati (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The higher the life expectancy, the more problems the elderly have. One of the problems faced is health problems due to the aging process such as hypertension and depression. The aim of the study was to determine the effect of warm water foot soak therapy on reducing blood pressure and depression levels with hypertension. This research is a quantitative research with pre-experimental research type with one group pretest-posttest design. The study was conducted at the Harapan Kita Elderly Social Institution in Palembang on March 28 to April 15, 2022. The population in this study was the elderly, totaling 30 respondents. Data was collected by measuring the blood pressure and depression level of the elderly before being given warm water foot soak therapy. The results of this study showed that the average systolic blood pressure before being given warm water foot bath therapy was 159.67 mmHg (95% CI: 156.65-162.69), with a standard deviation of 8.087 mmHg and the average diastolic blood pressure before therapy. warm water foot soak was 94.67 mmHg (95% CI: 90.90-98.43) with a standard deviation of 10.080 mmHg. The average level of depression before foot bath therapy was 6.966 (95% CI: 6.471-7.461) with a standard deviation of 1.325. The results of the diastolic test obtained a systolic value of 0.000, diastolic 0.000 and a depression level of 0.000, so it can be concluded that there is a significant difference between the values ??of systolic pressure, diastolic pressure and the level of depression in measurements after warm water foot soak therapy. The results of the study are expected to be a source of information for nursing home managers in providing nursing home services in overcoming blood pressure and depression using warm water foot soak therapy to strengthen non-pharmacological therapy in the elderly.